KEGIATAN PENANAMAN DAN PEMBAGIAN BIBIT OLEH MAHASISWA KKN DESA INDRA SAKTI UNRI - Annisa Qodriah,; Celvin Putri Ariana,; Farhan Fedora Illahi,; Fathur Raihan Joanda,; Madina, Madina; Muhammad Luthfi,; Putri Fricillia Soehardi,; Sefita Nahdia Syifa,; Shofi Nadhifa Defran, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
In dealing with the environmental crisis, greening is an important activity that is carried out conceptually. Indra Sakti Village is one of the villages that supports the greening program in an effort to save the environment. Community Service Program students and the community have succeeded in carrying out reforestation activities. Collaborating with the Pekanbaru forestry service as a distributor of seeds. Communities who have participated in the process of planting, maintaining and supervising reforestation activities are considered capable of continuing these activities in order to deal with the environmental crisis. Greening activities are carried out with various objectives, namely: supporting government programs, adding aesthetic value, providing economic benefits, dealing with environmental and air crises. Thanks to this activity, several vacant lands were successfully filled with plants and the participating communities also implemented this activity in their neighborhood vegetatively.